Parametric Optimisation of Micro Plasma Welding for Wire Arc Additive Manufacturing by Response Surface Methodology - Rosli, Nor Ana; Alkahari, Mohd Rizal; Ramli, Faiz Redza; Fadzli bin Abdollah, Mohd; Ikhwan Abdul Kudus, Syahibudil; Gazali Herawan, Safarudin (Manufacturing Technology Journal, 2022)
High deposition rate with minimal heat input is one of the primary emphases in wire arc additive manufacturing. This study aims to determine the optimal input parameters of micro plasma welding for single-layer deposition. The stability of a single layer is crucial as it serves as the foundation relative to the deposition of layers to avoid a discontinuous multi-layer material. The study focuses on wire feeding speed, welding speed, and pulse and their interaction between the input and response variables. Based on the study, the regression equation between the three key parameters and the response using the Box-Behnken Design response surface methodology was proposed. The outcome demonstrates that the op-timized sample deposition produces a smooth surface appearance with no apparent defects.
Keywords: additive manufacturing; 3D printing; wire arc additive manufacturing; micro plasma arc welding; response surface methodology